Theoretical-Methodological and Practice-Oriented Approach to Factor Analysis of the Performance of the Production Company in Management Decisions - Marina A. CHAPLYGINA; Viktoria B. PASECHKO; Irina N. Dorenskaya; Anzhelika A. Alyohina; Mariia A. Gololobova (Communications of International Proceedings, 2020)
In this article groups performance indicators, which in the economy of industrial and commercial companies include profit as an absolute indicator, and profitability as a relative indicator. The presented approach allows management to see the current situation in the management process, which negatively or positively affects the effective financial results of work (profit or uncovered loss). Therefore, the presented theoretical and methodological approach with a practice-oriented approach, including the use of a factor-based estimated method, gives financial analysts a reason to identify factors that negatively affect the profitability of companies and develop a strategy to eliminate them. The purpose of the research is to describe the theoretical, methodological and practice - oriented approaches of the factor method of performance analysis and demonstrate the calculation and analytical approach in the management process by relative and absolute values of profitability and efficiency of activities on the example of a production company.
Keywords: Performance indicator; asset profitability; profitability of sale; overall profitability; profitability of current assets; profitability of production assets.